Impacts of extreme weather events on bacterial community composition of a temperate humic lake - Hoke, Alexa; Woodhouse, Jason Nicholas; Zoccarato, Luca; McCarthy, Valerie; de Eyto, Elvira; Caldero-Pascual, Maria; Geffroy, Ewan; Dillane, Mary; Grossart, Hans-Peter (Prof. Dr.); Jennings, Eleanor (Water, 2020)
Extreme weather events are projected to increase in frequency and intensity as climate change continues. Heterotrophic bacteria play a critical role in lake ecosystems, yet little research has been done to determine how they are affected by such extremes. The purpose of this study was to use high-throughput sequencing to explore the bacterial community composition of a humic oligotrophic lake on the North Atlantic Irish coast and to assess the impacts on composition dynamics related to extreme weather events. Samples for sequencing were collected from Lough Feeagh on a fortnightly basis from April to November 2018. Filtration was used to separate free-living and particle-associated bacterial communities and amplicon sequencing was performed for the 16S rRNA V4 region. Two named storms, six high discharge events, and one drought period occurred during the sampling period. These events had variable, context-dependent effects on bacterial communities in Lough Feeagh. The particle-associated community was found to be more likely to respond to physical changes, such as mixing, while the free-living population responded to changes in nutrient and carbon concentrations. Generally, however, the high stability of the bacterial community observed in Lough Feeagh suggests that the bacterial community is relatively resilient to extreme weather events.